Numerical simulation of a slow extraordinary wave in magnetoactive plasma - Frolov, A. A.; Chizhonkov, E. V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2020)
The effect of an external magnetic field on plane non-relativistic nonlinear plasma oscillations is studied numerically and analytically. A method for the initialization a slow extraordinary wave in a magnetoactive plasma is proposed for constructing the missing initial conditions based on solving a linear problem using the Fourier method. For the purpose of numerical simulation of a nonlinear wave, a scheme of the second-order accuracy finite difference method of the MacCormack type based on Euler variables is constructed. It is shown that, when the external magnetic field is taken into account, the Langmuir oscillations are transformed into a slow extraordinary wave whose energy vibrates when moving from the origin. In this case, the wave velocity increases with the growth of the external constant field, which contributes to the removal of energy from the initial region of localization of oscillations.